2020
DOI: 10.1002/alr.22489
|View full text |Cite
|
Sign up to set email alerts
|

The cotton test redistributes nasal airflow in patients with empty nose syndrome

Abstract: Background: Empty nose syndrome (ENS) remains a controversial disease primarily associated with inferior turbinate tissue loss. Co on placement into the inferior meatus o en alleviates ENS symptoms within minutes, but the physiologic explanation for this phenomenon is unknown. Computational fluid dynamics (CFD) was employed to evaluate the mechanisms of altered nasal airflow conferred by co on testing. Methods:Six ENS patients (12 sides) with pre-existing sinus computed tomography (CT) imaging were enrolled a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 21 publications
(30 reference statements)
1
21
0
Order By: Relevance
“…Patients anecdotally report an increased, satisfying sense of “ability to draw air into their nose” following IMAP procedure. This change of airflow profile is highly consistent with CFD results from our previously published cotton test with contrast labeling, 13 although this theory requires more rigorous downstream testing.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Patients anecdotally report an increased, satisfying sense of “ability to draw air into their nose” following IMAP procedure. This change of airflow profile is highly consistent with CFD results from our previously published cotton test with contrast labeling, 13 although this theory requires more rigorous downstream testing.…”
Section: Discussionsupporting
confidence: 87%
“…We found that successful in-office cotton testing placement generated a dramatic clinical benefit that also resulted in an impressive shift in the nasal airflow distribution and promoted inferior mucosal airflow and mucosal stimulation. 13 Thus, the goal of this study was to use a similar approach to characterize changes in the profile of nasal airflow in ENS patients 6 months after IMAP surgery so that we may further understand the physiologic mechanisms driving the symptomatic improvement with tissue replacement surgery. We hypothesized that the restoration of inferior turbinate tissue bulk via IMAP would alter the characteristic ENS airflow pattern to the middle meatus, 11,12 and result in increased perception of airflow.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…52 The utility of nasal implants are based on potential changes in airflow dynamics. 53,54 A number of studies and systematic reviews of surgical intervention in ENS noted improvement in patient-reported sinonasal symptoms after surgical implants. 55-59…”
Section: Discussionmentioning
confidence: 99%
“…Treatment options for ENS should include medical and procedural interventions. Procedural interventions vary but all have the same intention of creating tissue bulk to redistribute air flow to other areas of the nose that have proper trigeminal nerve function 7–9 . These treatment options can include injection of submucosal fillers or surgical augmentation of the inferior meatus 7,9 .…”
mentioning
confidence: 99%